: Adaptabilidad laboral y ansiedad en personal administrativo. Gobierno Autónomo Descentralizado Municipal. Chambo, 2021 - Amaguaya Palmay Jhonatan Javier (2021)
ABSTRACT: The present research analyzed the cognitive profile of emotional dependence in students of the Physical and Sports Therapy Career of the National University of Chimborazo in 2020, the methodology used has a quantitative, bibliographic and field approach, the design is non- experimental and cross-sectional, the level is descriptive and correlational, the population consisted of 425 students, the sample is 228 students chosen through a non-probabilistic convenience sampling. The results obtained from emotional dependence are 25% medium level and 0.9% high level, the factors of emotional dependence that predominate are separation anxiety and affective expression of the partner; The relevant cognitive distortions are: Divine Reward Fallacy with 23.24%, Filtering with 20.17%, and Catastrophic Vision with 13.6%, the maladaptive schemes that stand out are: Self-sacrifice with 22.8%, Abandonment with 21.92%, Distrust / Abuse with 21.5%. Emotional dependence is a problem present in university students and little taken into account, which is why a cognitive profile was structured with cognitive distortions and maladaptive schemes that serve to understand this conflict from a cognitive approach.